Severe bone pain as first presentation of gastric malignancy - Mohammed, Tijjani; Alhaji, Samaila; Muhammad, Borodo; Kumo, Bello (Nigerian Journal of Basic and Clinical Sciences, 2026)
Gastric cancer still accounts for significant cancer mortality world-wide. It generally occurs at advanced ages in most parts of the world but reports in Nigeria so far indicates that gastric carcinoma is seen in younger ages. Most cases of gastric cancer present late; with weight loss, abdominal pain/swelling, anorexia, and vomiting with or without hematemesis. Presentation with bone pains is uncommon. We report a 23-year-old female Nigerian who presented with generalized bone pain with limitation of movement, use of non-steroidal anti-inflammatory drugs and recurrent hematemesis. She was resuscitated and further evaluation revealed; anemia, hypercalcaemia, and X-ray osteolytic lesions, suggestive of multiple myeloma. Bone marrow aspiration cytology however, showed heavy infiltration with clusters of abnormal cells suggestive of mucin secreting adenocarcinoma. Upper gastrointestinal endoscopy revealed gastric tumor, histologically confirmed to be a poorly differentiated adenocarcinoma. Gastric cancer typically presents late and in advanced stages. Typical symptoms may include, weight loss, abdominal pain, vomiting, and hematemesis. It may however present with metastasis to the bone and present with bone pains. It is recommended that evaluation of patients with bone pain should include upper gastrointestinal endoscopy especially, where anemia or upper gastrointestinal bleeding is co-existent.
Keywords: Bone pain; cancer; first; gastric; presentation